(untitled) (Global Scientific Review, 2025)
This article provides a brief overview of the emergence of the "Young Khivans" movement, its goals and objectives, its members, their activities, and the challenges faced by the movement. It also addresses the coverage of these activities in the media, as well as the activities of the right-wing and left-wing factions.